Chapter Textiles Market in 16th-Century Seville: Business and Mercantile Groups - Fernández Chaves, Manuel Francisco (Atti delle «Settimane di Studi» e altri Convegni, 2019)
This work offers a new interpretation about the main groups implicated in the textile trade in Seville during the 16th century, proposing a new chronology concerning the substitution processes happened between them and the nature of the importance of those groups. This is specially clear in the longer endurance of the activity of castilian and mainly burgalese merchants in the importation of canvas, and also is remarkable the growing importance of the Castilian producction of clothes and silk (also in the Valencian case), covering an increasing share of the Peninsular and the American demand, existing cases of cooperation between those different groups.